2015
DOI: 10.1037/pas0000021
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing DSM–5 nonsuicidal self-injury disorder in a clinical sample.

Abstract: The entry for nonsuicidal self-injury (NSI) disorder in the 5th edition of the Diagnostic and Statistical Manual o f Mental Disorders provides a criterion-based definition of clinically relevant NSI. NSI disorder is currently classified in the DSM-5 as a condition requiring further study. The present study aimed to examine the reliability, validity, and clinical utility of a self-report measure of NSI disorder, the Alexian Brothers Assessment of Self-Injury (ABASI). The sample included 511 patients admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
106
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(125 citation statements)
references
References 33 publications
9
106
1
7
Order By: Relevance
“…Another study also validating a selfreport measure of NSSI disorder in 511 patients found a prevalence of 74% of NSSI disorder in patients treated for NSSI. However, the authors proposed limited utility for NSSI disorder as a dichotomous diagnosis, but suggested the implementation of a dimensional approach to NSSI disorder (Washburn et al, 2015). In a systematic review on research conducted on NSSI disorder, Selby et al (2015) suggest further research on NSSI in five major areas in order to validate NSSI disorder to be included in the next DSM.…”
Section: Introductionmentioning
confidence: 98%
“…Another study also validating a selfreport measure of NSSI disorder in 511 patients found a prevalence of 74% of NSSI disorder in patients treated for NSSI. However, the authors proposed limited utility for NSSI disorder as a dichotomous diagnosis, but suggested the implementation of a dimensional approach to NSSI disorder (Washburn et al, 2015). In a systematic review on research conducted on NSSI disorder, Selby et al (2015) suggest further research on NSSI in five major areas in order to validate NSSI disorder to be included in the next DSM.…”
Section: Introductionmentioning
confidence: 98%
“…Among those with EDs, a recent meta-analysis reported a lifetime history of NSSI of 32.7% among those with bulimia nervosa (BN) and 27.3% among those with anorexia nervosa (AN) (Cucchi et al, 2016). Among those with NSSI, one study found 19.4% of participants with a history of NSSI also experience ED symptoms (Muehlenkamp et al, 2012), while another study found 29.9% of people being treated for NSSI engaged in binging, purging, or food restriction (Washburn et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…While the proposed criteria have received initial empirical support (e.g., Glenn and Klonsky, 2013), they showed poor inter-rater reliability in the DSM-5 field trials (Regier et al, 2013). Recent studies have raised concerns about the clinical utility of criterion A and B because few differences have been identified between individuals who meet diagnostic criteria for NSSI disorder and those with a history of NSSI but don't meet the disorder criteria in both community and clinical samples (e.g., Andover, 2014; Muehlenkamp and Brausch, in press; Washburn et al, 2015). These studies indicate a strong need to further investigate the validity and utility of the different DSM-5 criterion sets.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that were published well before the DSM-5 (APA, 2013) criteria indicate that almost all individuals who engage in NSSI report at least one function of the behavior, which is most commonly some form of affect regulation (Klonsky, 2007). Initial investigations of the DSM-5 criterion B have generally revealed that identifying specific functions has limited clinical utility, with one study finding that 87.7% of a sample of patients with current NSSI reported at least one function of NSSI and almost 25% reported all three functions assessed (Washburn et al, 2015). Almost all participants (98%) in an adolescent inpatient sample who met Criterion A reported affect regulation as a function of their NSSI, followed by marking distress (89%), self-punishment (88%), and anti-dissociation (88%), again indicating that functions of NSSI may not be adding diagnostic utility to NSSI Disorder (Glenn and Klonsky, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation